Investigation of Short-wave Diathermy Genotoxic Effect in Patients with Knee Osteoarthritis - Önder Şener; Sami Hizmetli; Ahmet Karadağ; Emrullah Hayta (Galenos Yayinevi, 2019)
Objective:Short-wave diathermy (SWD) is a physical therapy agent that is commonly used as a deep heater in physical medicine practices. The aim of this study was to investigate whether there is a chromosomal damage arising from therapeutic SWD by using micronucleus (MN) method.Materials and Methods:Thirty patients who suffered from knee pain, and diagnosed as gonarthrosis according to American College of Rheumatology criteria were admitted in the present study. Twenty patients were assigned as the treatment group (group 1) and 10 patients were assigned as the control group (group 2). The patients in the treatment group received 10 sessions of SWD therapy, whereas the patients in the control group received 10 sessions of sham SWD therapy. Peripheral venous blood was obtained from both the treatment and the control groups before and after 10 sessions of SWD therapy to evaluate MN scores. The scores of MN assessed before the therapy were compared with the MN scores at the end of 10 sessions of SWD therapy in the treatment and the control groups. Pre-treatment and end of the 10th session MN scores were compared between the treatment and the control groups.Results:There was not a statistically significant difference in MN scores between pre-treatment and after 10th session SWD therapy in both groups (p>0.05). There was also not a significant difference in the MN scores of the groups between pre-treatment and after 10th session of SWD therapy (p>0.05).Conclusion:In this study, we observed that the therapeutic SWD did not induce an increase in MN score, which is a sign of cytogenetic damage.